Finite Element Computation for Solving Pulsatile Blood Flow: Relevance in Assessing the Flow Dynamics in Abdominal Aortic Aneurysms - Vijayajothi , Paramasivam; Nenad , Filipovic; Kanesan , Muthusamy; Mohammed Rafiq Abdul Kadir (2010)
The objective of this paper is to present the mixed velocity-pressure (v-p) finite element method that solves the pulsatile blood flow in arteries. The solution exploits the Galerkin method and the fully implicit incremental-iterative procedure for the three-dimensional nonlinear finite element equations. This methodology is applied to model biological flows that are important in predicting growth and rupture risks in abdominal aortic aneurysms (AAA). The numerical technique was validated with the analytical solution of the Womersley model. Next, a physiologically realistic pulsatile blood flow waveform was imposed onto the idealized cylindrical arterial model and solved as a benchmark problem. The model represents a healthy abdominal aorta.This pulsatile condition simulates an in vivo aorta at rest. The numerical results were used to quantify clinically relevant flow dynamics that play a significant role in today’s field of medical treatment planning and development of predictive methods via computational modelling for assessing common clinical problems such as AAAs. (Authors' abstract)